An investigation into the geography of corporate e-commerce sales in the UK grocery market. (July 2019) - Kirby-Hawkins, Elena; Birkin, Mark; Clarke, Graham
E-commerce is one of the fastest growing sectors of the UK retail economy. The vast and rapid expansion of internet usage has generated widespread on-line sales, making the UK one of the leading countries for e-commerce. There have been a number of important papers on the geodemographics of e-commerce usage based on the results of surveys. These have shown that geography is important in understanding e-commerce sales: especially when we disaggregate sales by age and social class for example. However, there have been fewer studies analysing the geography of actual on-line sales provided by retail companies. The aim of this paper is to investigate the geography of e-commerce activity in more detail, especially as seen in UK grocery retailing. It will be concerned exclusively with transactions between businesses and consumers rather than either business to business or consumer to consumer. The paper makes extensive use of newly acquired data from a major UK grocery retailer to investigate the spatial patterns in the locations of their on-line consumers (we shall subsequently refer to this as 'partner data'). This will enable us to build on the survey-based analysis in previous studies to explore the main drivers of on-line expenditure in more detail.